2008
DOI: 10.1108/13522750810901501
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the expectations and preferences of complaining customers by combining the laddering interviewing technique with the Kano model of customer satisfaction

Abstract: PurposeThe purpose of this paper is to focus on complaint satisfaction with a particular emphasis on the qualities and behaviours that affect customers during personal complaint handling encounters.Design/methodology/approachFollowing a literature review of complaint satisfaction and the role of customer contact employees in complaint encounters, an exploratory study using both the laddering interviewing technique and Kano questionnaires is presented.FindingsThe laddering results indicate that being taken seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…It appears that students take the professors ability to listen carefully to what they have to say during the service recovery encounter almost for granted (the attribute is close to the area of basic factors), indicating that its absence will have serious results for higher education institutions. This corroborates previous research by Gruber, Reppel, Szmigin & Voss (2008) who showed that complaining customers take the frontline employee's ability to listen actively to them for granted. Professors have to realise that they cannot impress their complaining students just by listening to them actively, as they already expect this behaviour.…”
Section: Impact Of Professor Attributes On Students' (Dis)satisfactiosupporting
confidence: 81%
“…It appears that students take the professors ability to listen carefully to what they have to say during the service recovery encounter almost for granted (the attribute is close to the area of basic factors), indicating that its absence will have serious results for higher education institutions. This corroborates previous research by Gruber, Reppel, Szmigin & Voss (2008) who showed that complaining customers take the frontline employee's ability to listen actively to them for granted. Professors have to realise that they cannot impress their complaining students just by listening to them actively, as they already expect this behaviour.…”
Section: Impact Of Professor Attributes On Students' (Dis)satisfactiosupporting
confidence: 81%
“…For example, recent studies show that when monetary compensation is delivered in a speedy manner, it has a stronger effect than delayed monetary compensation (Roschk and Gelbrich, 2014). Rapid problem resolution makes consumers feel happy by saving them time, even when time was not their main concern when they first complained (Gruber et al, 2008). It is also known that consumers whose main objectives are to seek redress prefer real-time interaction with companies, such as phone or face-to-face conversations, as opposed to indirect methods such as letters (Mattila and Wirtz, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the substantial work done in the area of customer feedback management, most of the research conducted so far focuses on customer complaints and dissatisfaction. The customer complaining field was pioneered by Best and Andreasen (1977) and thereafter has been the emphasis of many scholars (Gruber et al, 2008;Henneberg et al, 2015), leaving the various manifestation of PCF quasi-marginalized (Nasr et al, 2014). We do not deny the merits of these robust studies in advancing the area of customer feedback management, where both valences of customer feedback have been acknowledged and considered (Ordenes et al, 2014), but we do propose a complimentary in-depth look at personal PCF.…”
Section: Positive Customer Feedbackmentioning
confidence: 91%